p53-regulated SESN1 and SESN2 regulate cell proliferation and cell death through control of STAT3 - Haidurov, Alexander (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2024)
Sestrins (SESN1-3) are evolutionarily conserved, stress-responsive proteins known for their significant roles in regulating cellular stress, homeostasis, and metabolism. Initially identified as a target of p53, a critical protein for maintaining genome stability, Sestrins have since been recognised for their response to various stresses, including oxidative, ER, and metabolic stresses. Despite their established role in inhibiting the mTORC1 complex, our research on A549 lung adenocarcinoma cells reveals that SESN1&2 suppress cell proliferation and support apoptosis through mechanisms independent of mTORC1, notably involving the regulation of STAT3. Employing the CRISPR/Cas9 technology, we generated SESN1&2 knockout A549 cells to study the role of SESN1&2 in cellular signalling, particularly under conditions of genotoxic stress. We discovered that the inactivation of SESN1&2 leads to the upregulation of STAT3, a transcription factor frequently activated in human cancers and associated with pro-proliferative and anti-apoptotic gene expression. Its activation is a common feature in many cancers, including lung carcinoma, contributing to cancer progression and drug resistance. Our study demonstrates that the absence of SESN1&2 confers resistance to cisplatin and etoposide, chemotherapeutic drugs used to combat cancer. This resistance mirrored the effect we have demonstrated with p53 knockdown, highlighting the relationship of SESN1&2 and p53 in DNA damage-induced apoptosis. Our search for the mechanism by which SESN1&2 support p53-induced apoptosis led us to find that the inactivation of SESN1&2 leads to increased STAT3 activity through the downregulation of PTPRD, a phosphatase responsible for STAT3 dephosphorylation. In this context, Sestrin support of PTPRD transcription may result in the dephosphorylation of STAT3, leading to the downregulation of anti-apoptotic factors such as MCL1, thereby promoting apoptosis. These findings suggest a novel mechanism where SESN1&2 deficiency can lead to cancer proliferation and drug resistance, suggesting a crucial role for SESNs in cancer biology beyond their antioxidative and mTORC1-inhibitory functions. Our proposed mechanism is that SESN1&2 are crucial to mediating p53-dependent suppression of STAT3 activity via PTPRD in an oncogenic context. This maps out a novel signalling axis for cell survival and proliferation. Given the global health burden of cancer, with lung cancer being the most diagnosed and leading cause of cancer deaths, understanding and targeting the SESN-STAT3 axis could offer new avenues for therapeutic interventions. Our research advances the fundamental understanding of Sestrin biology and lays the groundwork for potential strategies for cancer treatment, such as activation of SESN1&2 as a promising approach for managing lung cancer.
APPROVED
Keywords: Cancer; STAT3; SESN1; SESN2; p53; Lung Cancer; Cell Death